Peran Pendidikan Agama Kristen dalam Membangun Toleransi di Masyarakat Majemuk - Melkisedek Melkisedek; Marni Marni; Semuel Linggi Topayung; Melisusanti Beli (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2025)
Christian Religious Education (PAK) plays a crucial role in building religious tolerance in a diverse society. PAK does not only focus on Christian teachings, but also seeks to shape students' morals, attitudes, and spirituality through an approach that is relevant to various age levels. Thus, this education provides a solid foundation for understanding universal human values. PAK emphasizes the importance of tolerance in a pluralistic society, respects religious diversity, and accepts differences as part of a complex social structure. In this context, PAK teaches students to see differences as a source of strength and cultural richness, not as a barrier. This education also encourages the development of empathy and concern for others, which are very important in building intergroup relationships.Furthermore, PAK actively seeks to expand understanding of the values ​​of commonality between religions through dialogue and seminars. These activities involve not only students but also parents and local communities and create constructive discussion forums. Using social media as a means to spread messages of taboos and respond quickly to religious issues is also an effective strategy given its broad impact. PAK also contributes to poverty alleviation and community empowerment, regardless of religion, with programs that focus on improving basic needs and quality of life.A commitment to justice and human rights is the foundation of all initiatives, and all stakeholders are asked to play an active role in creating positive change. Therefore, PAK aims to build a peaceful, harmonious, and inclusive society that values ​​differences and avoids conflict. Through continuing education and open dialogue, our goal is to equip future generations with an attitude of mutual respect and harmonious coexistence with diversity.